The state, the market, and development - Joseph E. Stiglitz (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2016)
The state has played a major role in the most important developmental successes. This paper discusses the advances in our understanding of the role of the state in the developmental process over the past thirty years, and the contribution to those advances played by changes in economics, changes in the world, and key experiences (in particular the successes in East Asia and the failures in the countries pursuing Washington Consensus policies).
Keywords: 330; state; Washington Consensus; industrial policies; development; inequality